Pengaruh Black Carbon Dan Sulfur Terhadap Koefisien Grip Bahan Ban Dengan Batikan Silang Pada Lintasan Aspal Basah Dan Kering - Gunawan, Indra; , Ir. Pramuko IP.,MT (2016)
Tires are an important part of a land vehicle that works by utilizing a surface friction force between the road surface is called the grip, one of the factors that affect tire grip is the quality of the compound. This study aims to determine the effect of black carbon and sulfur to the coefficient of grip compound tire material with a cross on the tarmac batikan wet and dry conditions, study the effect of black carbon and sulfur composition of the value of its hardness and strength. Material for tire compound used is natural rubber and synthetic rubber SBR RSS mixed with chemicals carbon black, white oil, ZnO, strearic acid, prafin wax, MBTS, cumaron resin and sulfur, mixed use tools rollingmixing to form sheets. Rheometer testing is done to determine the value kematang after it is vulcanized with a cross in the mold batikanvulkanizing machine press. Hardness testing using test equipment shore hardness tester with ISO standards. Tensile test using a rubber test equipment testing equipment with ISO standards. Testing the coefficient of grip with the loading test apparatus using grips with the basic principle of the power equation. Testing wear the cross tread pattern tarmac wet and dry conditions using a constant load of 16.2 kg for 30 minutes. Based on the results of tests performed variations of black carbon and sulfur in each compound affects the value of the coefficient of grip, keausannya value, the value of its hardness and strength values. For example the first composition by administering the compound as black carbon and sulfur by 50/3 Phr has the highest grip coefficient with a value of 0.982 for a load of 21.2 kg, while for compound 3 with the black carbon and sulfur by 60/4 Phr has a coefficient grip lowest amounting to 0.968 with the same load on the tarmac in wet conditions.